2019
DOI: 10.1186/s12872-019-1080-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental health and obstructive coronary artery disease: an observational study

Abstract: Background The association between dental health and coronary artery disease (CAD) remains a topic of debate. This study aimed to investigate the association between dental health and obstructive CAD using multiple dental indices. Methods Eighty-eight patients (mean age: 65 years, 86% male) were prospectively enrolled before undergoing coronary CT angiography ( n = 52) or invasive coronary angiography ( n = 36). Obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Our findings also demonstrated that both edentulism and periodontitis are related to CAD and the edentulism could increase the odds ratio of CAD, like periodontitis. These results are consistent with studies showing an association between tooth loss and CAD 18,19,32,34,61‐63 . Zanella et al 18 found a significant interrelation between numerous tooth loss and vascular occlusion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings also demonstrated that both edentulism and periodontitis are related to CAD and the edentulism could increase the odds ratio of CAD, like periodontitis. These results are consistent with studies showing an association between tooth loss and CAD 18,19,32,34,61‐63 . Zanella et al 18 found a significant interrelation between numerous tooth loss and vascular occlusion.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with studies showing an association between tooth loss and CAD. 18,19,32,34,[61][62][63] Zanella et al 18 found a significant interrelation between numerous tooth loss and vas- and they showed that CHD group had remarkably less teeth rather than the control group. In a meta-analysis study consisted of cohort studies, Bahekar et al 63 showed that subjects having less than 10 teeth exhibited 1.24 times more likely to develop CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The link between periodontal disease and angiographically verified coronary disease has been well established in stable coronary artery disease and acute coronary syndromes [ 20 , 21 , 22 , 23 ]. Nonetheless, it is still a matter of debate whether PD is an independent risk factor for CAD or whether the association is based on an abundance of shared risk factors, including, amongst others: age, gender, smoking, diabetes mellitus, hypertension, obesity, low socioeconomic status, and stress [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The form, which was created by the researchers by reviewing the literatüre [1][2][3][4][5], evaluating the sociodemographic characteristics of the individuals and their status related to dental treatment and cardiovascular disease (19 items) was used to collect data. The study also used a questionnaire to determine the presence of infective endocarditis signs and symptoms (11 items; yes, no; 2-point Likert type), the risk of developing infective endocarditis (20 items; yes, no; 2-point Likert type), and the level of knowledge of Oral Dental Health and Infective Endocarditis (17 items; strongly disagree, disagree, undecided, agree, strongly agree; 5-point likert type) created by the researchers in accordance with the literatüre [5][6][7][8][9][10]. The questionnaire used in the study consists of 67 items in total.…”
Section: Data Collection Toolsmentioning
confidence: 99%